2004
DOI: 10.1124/mol.65.6.1415
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin Potentiates Wild-Type and Mutant Cystic Fibrosis Transmembrane Conductance Regulator Chloride-Channel Currents

Abstract: To examine the effects of capsaicin on cystic fibrosis transmembrane conductance regulator (CFTR), we recorded wildtype and mutant CFTR chloride-channel currents using patchclamp methods. The effects of capsaicin were compared with those of genistein, a well-characterized CFTR activator. In whole-cell experiments, capsaicin potentiates cAMP-stimulated wild-type CFTR currents expressed in NIH 3T3 cells or Chinese hamster ovary cells in a dose-dependent manner with a maximal response ϳ60% of that with genistein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
59
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 44 publications
4
59
1
Order By: Relevance
“…The short-term effect of potentiators on mutant CFTR channel activity in detailed patchclamp studies suggests that they may interact directly with the mutant protein (Cai and Sheppard, 2002;Ai et al, 2004). Consistent with this idea, we showed recently that the shortterm addition of 4-methyl-2-(5-phenyl-1H-pyrazol-3-yl)phenol (VRT-532) to isolated membranes expressing the F508del-CFTR protein modified its conformation and susceptibility to trypsin-mediated proteolysis (Wellhauser et al, 2009).…”
Section: Introductionsupporting
confidence: 67%
“…The short-term effect of potentiators on mutant CFTR channel activity in detailed patchclamp studies suggests that they may interact directly with the mutant protein (Cai and Sheppard, 2002;Ai et al, 2004). Consistent with this idea, we showed recently that the shortterm addition of 4-methyl-2-(5-phenyl-1H-pyrazol-3-yl)phenol (VRT-532) to isolated membranes expressing the F508del-CFTR protein modified its conformation and susceptibility to trypsin-mediated proteolysis (Wellhauser et al, 2009).…”
Section: Introductionsupporting
confidence: 67%
“…41 Therefore, putative binding sites on the nucleotide-binding domains of CFTR Cl -channels are proposed to be target(s) for many CFTR activators. 42,43 However, our data indicate that the primary mechanism of single CFTR Cl -channel activation by N20 may not involve the nucleotide-binding domains or regulatory domain of CFTR, because these sites have been previously stimulated by ATP and protein kinase A. Therefore, we cannot rule out the possibility that N20 may in some way influence structural changes in the transmembrane domains of CFTR Cl -channels, resulting in channel activation.…”
contrasting
confidence: 39%
“…After biosynthetic rescue and delivery to the cell surface, ⌬Phe508-CFTR exhibits phosphorylation dependent and ATP regulated chloride channel activity, albeit with altered gating in mammalian cells (Wang et al, 2000). Other small molecules, such as genistein (Hwang et al, 1997), capsaicin (Ai et al, 2004), and, more recently, VRT-532 (Van Goor et al, 2006), were found to enhance or "potentiate" the open probability of ⌬Phe508-CFTR after its biosynthetic rescue and phosphorylation at the cell surface. The latter compound was subsequently shown to also function as a "corrector" rescuing the surface expression of ⌬Phe508-CFTR (Wang et al, 2006).…”
mentioning
confidence: 99%
“…As in the case of VRT-532, both of these potentiators act to enhance the open time of ⌬Phe508-CFTR single channels after prephosphorylation by protein kinase A. Ai et al (2004) suggested that potentiators may act to stabilize the NBD1-NBD2 heterodimer, possibly by preventing ATP hydrolysis. The measurements of reduced ATP hydrolysis by ⌬Phe508-CFTR after incubation with VRT-532 provide direct evidence to support this hypothesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation